Spin-polarized electron tunneling between charge-density-wave metals: Электpонные свойства металлов и сплавов - Ekino, T.; Gabovich, A.M.; Voitenko, A.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
For junctions between metals partially gapped by charge density waves (CDWs), the quasiparticletunnel currents J(V) and conductances G(V) in external magnetic fields H are calculatedas functions of H, the bias voltage V, temperature T, the dielectric gaps ∑, and the gapped portionsm of the Fermi surface (FS). The paramagnetic effect of H is taken into account, whereas orbitaleffects are neglected. General expressions are obtained for different CDW metal electrodes.Analytical formulas are obtained for T = 0. Explicit numerical calculations are carried out for symmetrical junctions. The results are substantially unlike those for junctions between superconductors.It is shown that due to the interplay between quasiparticles from nested and non-nested FS sections the junction properties involve features appropriate to both symmetrical and asymmetrical setups. In particular, for H = 0 discontinuities at eV=±2∑ and square-root singularities at eV =±∑ should coexist. Here e is the elementary charge. For H ≠ 0 the former remain intact, while the latter split. It is suggested to use the splitting as a verification of the CDW nature of the pseudogap in high-Tc superconducting oxides.